PENGARUH KEPUTUSAN INVESTASI, PENDANAAN, KEBIJAKAN DIVIDEN, DAN TINGKAT SUKU BUNGA TERHADAP NILAI PERUSAHAAN - Yunitasari, Dewi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the influence of investment decision, financing decision, dividend policy, and interest rate to the companyâs value.The population is real estate and property companies which are listed in Indonesia Stock Exchange (IDX). In this research, the sample collection technique has been determined by using purposive sampling and it has obtained 8 samples of real estate and property companies which distribute their dividend share continuously in 2009-2012. This research is using multiple linear regressions. The result of research shows that: (1) the investment decision has significant influence to the companyâs value and it shows unidirectional relation. (2) Financing decision has significant influence to the companyâs value yet the negative coefficient shows non-unidirectional relation. (3) The dividend policy has significant influence to the companyâs value yet the negative coefficient shows non-unidirectional relation. (4) The interest rates have no significant influence to the companyâs value yet negative coefficient shows non-unidirectional relation.Keywords: Investment Decision, Financing Decision, Dividend Policy, Interest Rates, Companyâs Value.